Inclusion of dietary β-mannanase improves performance and ileal digestibility and reduces ileal digesta viscosity of broilers fed corn-soybean meal based diet. (16th May 2018) - Balasubramanian, B; Ingale, S L; Park, J Hong; Rathi, P C; Shanmugam, S; Kim, I H
ABSTRACT: This study was aimed to evaluate the influence of dietary β-mannanase inclusion on growth performance, apparent ileal digestibility, digesta viscosity, blood metabolites and excreta noxious gas emissions in broilers fed corn-soybean meal based diet. A total of 600 conventional healthy 1-d-old ROSS 308 broilers with body weight 45 ± 0.50 g (mean ± SD) were randomly assigned to 4 dietary treatments with 10 replicates cages, with 15 broilers in each and fed basal diet supplemented to corn-SBM based diets with 0, 2400, 4800, and 7200 MNU β-mannanase/kg for 35 d feeding trial period. Significant results were observed on improved average daily gain and reduced feed conversion ratio during trial period and also reduced ileal digesta viscosity and improved apparent ileal digestibility of dry matter, nitrogen and energy. However, no significant effects were found on blood urea nitrogen and creatinine, excreta noxious gas emissions. In conclusion, the inclusion of dietary β-mannanase had potential to improve daily gain and feed efficiency and apparent ileal digestibility while decreasing digesta viscosity of broiler.